Gender roles in Pina Weaving the case of Banga, Aklan - Dimapilis, Eda Fidel (2003)
This study was conducted to identify the gender roles in piña weaving in Banga, Aklan. The specific activities and responsibilities in the production process in order to understand the issues and concerns that affect the gender performance in the piña weaving industry: and, to understand significant opportunities that gender development can contribute towards the promotion of piña weaving as a potential leading industry of Aklan. The study was conducted in Banga, one of the municipalities of Aklan, where more than 80% of the country's piña product are being produced. A total sample of 60 respondents was selected through purposive sampling. The study covered the month from July to September 2003. The study revealed that the average age of the repsondent was 36 years in both male and female. Out of 60 respondents 93% were female and only 7% are male. Majority of them finished secondary education. The average year in piña weaving was 11.25 years and more that 60% of the respondents had 2-3 household members engaged in weaving. 55% of the weavers were cooperatives members. Average time spent by the men and women differ at each processing stage of piña cloth production. The average time spent by male respondents on fiber processing was higher with a total mean of 6.8 hours than the women with only 5.6 hours. This can be accounted to the physical requirement of the activity and the role by the women in doing many of the household chores. The most time consuming activity was warp and weft preparation with an average of 5.93 hours per day for female and 4 hours for males. Weaving and marketing ranks second with 5.37 hours spent. The tota; average time spent by female on weaving and marketing was 19.63 hours while male has only 13.25 hours per day. This only shows that women were more experienced than men in weaving. Average production per month of a weaver was 10.50 meters. Majority of the respondents weave only about 8.0-12.0 meters of piña cloth per month. The net income per month of a weaver ranged from P500.00-P3,024.00 with a mean of P1,614.67. Primary hindrance in piña weaving industry was lack of buyer and capital, and low price of piña cloth and inferior quality of raw materials were minor problems encountered by weavers.
Special Problem (Mgt 299-Research Methods in Management). -- [Iloilo City] : UPV-CM, August 2003.